Artificial Intelligence and its Ethical Connotations (Revista Iberoamericana de Bioética, 2024)
This manuscript succinctly addresses the footprint and ethical issues raised by the development and use of artificial intelligence in everyday life. Initially, we introduced the connotations of the interactions between artificial intelligence and people. Subsequently, in greater detail, it delves into its genesis, as well as the impact of its use, emphasizing essentially medicine and its ethical dilemmas that it poses in the use of health procurement in people.
Keywords: artificial intelligence; ethics; medicine; social dilemmas